'Anyone can have a mental illness': A qualitative inquiry of pre‐registration nursing students' experiences of traditional mental health clinical placements. (3rd November 2020) - Foster, Kim; Giandinoto, Jo‐Ann; Furness, Trentham; Blanco, Anthony; Withers, Elaine; Alexander, Louise
Abstract: Nurses play a crucial role in mental healthcare provision. Like many countries, Australian nursing students are educated in comprehensive pre‐registration programmes which include mental health clinical placements. Placements play a vital role in students' education, providing the opportunity to engage with consumers and develop mental health nursing knowledge and skills. There is limited knowledge of student perspectives on traditional placements in contemporary recovery‐oriented mental health services. This interpretive qualitative inquiry aimed to explore nursing students' experience of traditional mental health clinical placement and how it influenced their practice and their understandings of recovery from mental illness. Data were collected from focus groups with n = 31 nursing students in a large metropolitan public mental health service. Thematic analysis resulted in three themes of experience: humanizing people with mental illness; learning about recovery; and shifting perspectives on mental health nursing. Through a positive placement experience where they felt supported and included by staff, students came to see consumers as people rather than diagnoses, developed greater understanding of mental health nursing work and were more likely to consider mental health nursing as a career choice. Peer‐support workers were an important influence on students' understandings of recovery and have a key role to play in educating students on placement. Students need to be prepared and supported by university and clinical staff to deal with vicarious trauma that may occur on placement. Mental health placements play a crucial role in attracting students into the field, and it is imperative they remain part of comprehensive pre‐registration education.